Rethinking Global History (KULT_online, 2013)
The German essay collection Europa als Provinz. Perspektiven postkolonialer Geschichtsschreibung consists of essays by the Indian historian Dipesh Chakrabarty, some of which were published for the first time in Habitations of Modernity (2002) and Provincializing Europe (2001). It also contains a new foreword, an interview with the author, and two recent publications about global warming and climate change. Chakrabarty tries to illuminate why it makes sense to overcome the "imaginary figure" of Europe in social sciences as well as in the humanities, and shows which difficulties are associated with the project of "provincializing Europe". The book can be considered as a useful introduction to postcolonial historiography.